2020
DOI: 10.1101/2020.03.25.009084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-neuronal expression of SARS-CoV-2 entry genes in the olfactory system suggests mechanisms underlying COVID-19-associated anosmia

Abstract: Recent reports suggest an association between COVID-19 and altered olfactory function. Here we analyze bulk and single cell RNA-Seq datasets to identify cell types in the olfactory epithelium that express molecules that mediate infection by SARS-CoV-2 (CoV-2), the causal agent in COVID-19. We find in both mouse and human datasets that olfactory sensory neurons do not express two key genes involved in CoV-2 entry, ACE2 and TMPRSS2. In contrast, olfactory epithelial support cells and stem cells express both of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
353
0
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(391 citation statements)
references
References 105 publications
18
353
0
20
Order By: Relevance
“…Direct viral invasion of SARS-CoV and MERS-CoV is observed in multiple brain regions in human patients and mouse models 124,125 , consistent with widespread ACE2 expression in numerous brain cell types. Furthermore, SARS-CoV has been shown to infiltrate the brain via the olfactory epithelium-olfactory bulb axis 127 ; olfactory transmission for SARS-CoV-2 has been recently proposed 128 . Other possible transmission routes could be through the infection of ACE2 + TMPRSS2 + enteric neurons synapsing with vagal afferents, or entry through blood-CNS interfaces such as the choroid plexus or meninges 121,[129][130][131] .…”
Section: Discussionmentioning
confidence: 99%
“…Direct viral invasion of SARS-CoV and MERS-CoV is observed in multiple brain regions in human patients and mouse models 124,125 , consistent with widespread ACE2 expression in numerous brain cell types. Furthermore, SARS-CoV has been shown to infiltrate the brain via the olfactory epithelium-olfactory bulb axis 127 ; olfactory transmission for SARS-CoV-2 has been recently proposed 128 . Other possible transmission routes could be through the infection of ACE2 + TMPRSS2 + enteric neurons synapsing with vagal afferents, or entry through blood-CNS interfaces such as the choroid plexus or meninges 121,[129][130][131] .…”
Section: Discussionmentioning
confidence: 99%
“…Prior experimental studies of coronavirus have demonstrated that infection with human alphacoronavirus (HCoV-229E) disrupts ciliary nasal epithelium (Chilvers et al, 2001), a possible mechanism of olfactory dysfunction. Indeed, olfactory epithelial cells express the CoV-2 receptor, angiotensin-converting enzyme 2 (ACE2), yet the precise cellular subtype that may mediate anosmia in COVID-19 remains unclear (Brann et al, 2020). For both olfactory and gustatory perception, CoV-2 infiltration of higher-order structures within the CNS, or cranial nerves such as the vagus nerve, involved in signal transduction and chemosensory processing, may underlie their dysfunction (Bromley, 2019).…”
Section: Anosmia and Ageusiamentioning
confidence: 99%
“…11 A detailed study of nasal epithelium did not show TMPRSS2 presence in the neuronal component but did on the respiratory epithelium. 12 Notably, SARS-CoV was confirmed in postmortem neurons and glial cells of human patients with fatal systemic manifestations. 13 A non-peer-reviewed report claims there was a case of symptomatic encephalitis with detected SARS-CoV-2 in cerebrospinal fluid.…”
Section: Receptors For Viral Entry and Their Distributionmentioning
confidence: 99%